Genetic divergence and representative tomato pinworm populations subcollection - Moreira, Gisele Rodrigues; da Silva, Derly José Henriques; Picanço, Marcelo Coutinho; Peternelli, Luiz Alexandre; Caliman, Fabiano Ricardo Brunele (Pesquisa Agropecuaria Brasileira, 2004)
This work aimed to study the genetic diversity and to propose a representative tomato pinworm, Tuta absoluta (TDT), subcollection. Populations of insect originally from Uberlândia, MG, Viçosa (MG), Camocim de São Félix, PE, and Santa Teresa, ES, Brazil, and five tomato accessions, ‘Santa Clara’, ‘Moneymaker’, TOM-601, PI 126445 (Lycopersicon hirsutum f. typicum) and PI 134417 (L. hirsutum f. glabratum) were used. Grouping analysis (Tocher method, using the Mahalanobis distance as dissimilarity measurement) was performed and the relative importance of TDT characters to the genetic divergence among populations was evaluated by Singh method. The pinworm populations of each group obtained by grouping analysis were combined, and for each character, Student t test for one mean was performed. There is genetic variability among TDT populations collected from different regions of Brasil, when infested on Lycopersicon spp. The larval mortality contributed most to divergence among TDT populations, except for PI 134417, which had the number of female pupae as the characteristic of the highest contribution. A subcollection is proposed from combination of the Santa Teresa and Uberlândia populations.